Biomarker-guided antibiotic therapy—strengths and limitations - Nora, David (Ann Transl Med, 2017)
Biomarkers as C-reactive protein (CRP) and procalcitonin (PCT) emerged as tools to help clinicians to diagnose infection and to properly initiate and define the duration of antibiotic therapy. Several randomized controlled trials, including adult critically ill patients, showed that PCT-guided antibiotic stewardship was repeatedly associated with a decrease in the duration of antibiotic therapy with no apparent harm. There are however some relevant limitations in these trials namely the low rate of compliance of PCT-guided algorithms, the high rate of exclusion (without including common clinical situations and pathogens) and the long duration of antibiotic therapy in control groups. Such limitations weakened the real impact of such algorithms in the clinical decision-making process and strengthened the concept that the initiation and the duration of antibiotic therapy cannot depend solely on a biomarker. Future efforts should address these limitations in order to better clarify the role of biomarkers on the complex and multifactorial issue of antibiotic management and to deeply understand its potential effect on mortality.